2017
DOI: 10.1111/jar.12367
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of multicomponent weight management interventions for adults with intellectual disabilities

Abstract: BackgroundObesity is more prevalent in people with intellectual disabilities and increases the risk of developing serious medical conditions. UK guidance recommends multicomponent weight management interventions (MCIs), tailored for different population groups.MethodsAn integrative review utilizing systematic review methodology was conducted to identify the types of MCIs delivered to adults with intellectual disabilities.FindingsFive studies were identified. All of the studies' MCIs were tailored for adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…A recent systematic review (Doherty, Jones, Chauhan, & Gibson, ) investigated multicomponent weight management interventions (MCI) for adults with learning disabilities. Only two of the included studies reported clinically significant weight loss outcomes in participants with obesity, both associated with “TAKE 5,” an intervention tailored for obese adults with learning disabilities (Melville et al., ; Spanos, Hankey, Boyle, & Melville, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review (Doherty, Jones, Chauhan, & Gibson, ) investigated multicomponent weight management interventions (MCI) for adults with learning disabilities. Only two of the included studies reported clinically significant weight loss outcomes in participants with obesity, both associated with “TAKE 5,” an intervention tailored for obese adults with learning disabilities (Melville et al., ; Spanos, Hankey, Boyle, & Melville, ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have recently been conducted on the influence of sports activities on the physical condition of people with ID, and the results confirm the improvement in health status and self-perception [ 36 , 37 ]. A literature study on the construct of CE and its different nominations and applications [ 26 ] also shows the growing number of publications in this area of knowledge.…”
Section: Introductionmentioning
confidence: 83%
“…Reviews have been conducted to explore weight management interventions for adults with intellectual disabilities (Doherty, Jones, Chauhan, & Gibson, ; Hamilton et al, ; Harris, Melville, Murray, & Hankey, ; Jinks, Cotton, & Rylance, ; Spanos, Melville, et al, ). These reviews all found a lack of evidence‐based weight management interventions tailored to meet the needs of adults with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%